Strategi Pemasaran Desa Wisata untuk Meningkatkan Ekonomi Masyarakat di Kabupaten Kerinci - Gampo Haryono; Ayu Esteka Sari (LPPM - STIE SAKTI ALAM KERINCI, 2018)
Tourism is important for the economy of the community. Tourism is faced with the challenge of finding new strategies and methods to overcome competition. The tourism market is determined by tourism demand and tourism supply. An important feature of tourism's inflexibility, due to its basic supply element. In navigating the needs of the tourism market, the key role through its activities, especially through the marketing mix that can identify and distinguish tourism products offered. Marketing in tourism itself stems from the fact that products in tourism are services. With the help of marketing mix elements: products, prices, promotions, places, human resources, packaging and processes. The purpose of this study was to study the impact of tourism marketing with a marketing mix strategy that has an effect on power so as to improve the economy of the people around tourism objects and to determine the marketing elements that have the most impact on increasing tourism in Kerinci Regency. With the number of respondents is 132 people. The research model that will be used in this study is a tiered structure model and to test the proposed hypothesis used SEM (Structural Equation Modeling) analysis techniques which are operated through AMOS 18. The results of data processing show that competitiveness has a positive effect on the economic improvement of actors and activists tourism in Kerinci Regency. The marketing strategy of the tourism marketing mix studied in this study resulted in the product strategy and promotion influencing competitiveness which had an impact on improving the economy of tourism activists in Kerinci Regency. While price, distribution and human resources have no effect.